Ketersediaan Dan Aksesibilitas Pangan Lokal: Implikasinya Terhadap Ketahanan Pangan Di Distrik Konda Kabupaten Sorong Selatan Provinsi Papua Barat Daya - Krisna Fransina Lermating; Hendry Jems Yoel Aidore; Franklin D. Paiki (Jurnal Administrasi Terapan, 2024)
This study aims to analyze the availability and accessibility of local food and its implications for food security in Konda District, South Sorong Regency, Southwest Papua Province. Local food plays an important role in ensuring food security, especially in areas with limited access to external food sources. In this context, this study explores various factors influencing the availability and accessibility of local food, such as agricultural production, transportation infrastructure, the economic conditions of the community, and local government policies.Using qualitative and quantitative methods, data were collected through in-depth interviews, field observations, and questionnaire surveys of households in Konda District. The results of the study indicate that the availability of local food is influenced by traditional production patterns and limited access to modern agricultural technology. Additionally, food accessibility is also hampered by difficult geographical conditions and inadequate road infrastructure.This study finds that although the people of Konda District have a high dependence on local food, they face various challenges in ensuring long-term food security. This analysis provides deep insights into how improving the availability and accessibility of local food can significantly contribute to food security in the region. Proposed policy implications include infrastructure development, capacity building for local farmers, and the implementation of more efficient agricultural technologies.This research is expected to serve as a reference for local governments and relevant stakeholders in formulating effective strategies to enhance food security in Konda District and other areas with similar characteristics.Keywords: Food availability, food accessibility, food security, local food, Konda District, Southwest Papua